A guide to the common epiphytes and mistletoes of Singapore (Cengage Learning Asia, 2015)
This book is the first to profile the unique epiphytic plant communities found in Singapore. The canopies of tropical trees are often festooned with luxuriant masses of delicate ferns, orchids and mistletoes; these veritable aerial gardens are one of the most biodiverse habitats on the planet. Yet, despite their prevalence in tropical urban landscapes, many of these fascinating aerial plants remain unappreciated and misunderstood.